Zirconium metal-organic framework loaded nano platinum catalyst as well as preparation method and application thereof

By encapsulating platinum nanoparticles in a metal-organic frame to form a zirconium metal-organic frame-loaded nanoplatin catalyst, the problems of harsh conditions and unstable catalysts in the process of selective hydrogenation of furfurfural in the preparation of furfurfural furfurfural are solved, and the effect of efficient preparation of furfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfur

CN119793537AActive Publication Date: 2025-04-11WUHAN TEXTILE UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411905832.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing catalysts have harsh conditions in the preparation of furfurfural selective hydrogenation of furfurfural and unstable catalysts, which limits its practical application.

Method used

Using zirconium metal-organic frame-loaded nanoplatinum catalyst, the Zr-BBI frame was prepared by H4BBI and ZrCl4 as raw materials, and the platinum nanoparticles were encapsulated in the pores of the frame to enhance the interaction between platinum and the frame and improve catalytic activity and selectivity.

Benefits of technology

Furfurfural selective hydrogenation under mild conditions was achieved to prepare furfurfural alcohol, with the conversion rate of furfural reaching 100%, the selectivity of furfurfural alcohol reaching 94.5%, and the catalyst stability was improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793537A_ABST
    Figure CN119793537A_ABST
Patent Text Reader

Abstract

The invention provides a zirconium metal-organic framework loaded nano platinum catalyst and a preparation method and application thereof, and belongs to the technical field of catalysts for preparing furfuryl alcohol through selective hydrogenation of furfural, and the preparation method comprises the following steps: dispersing platinum nanoparticles in a first solvent to obtain a first mixed solution; mixing bis-imidazole tetracarboxylic acid with zircon salt, adding a second solvent and an acidity regulator, and uniformly mixing to obtain a second mixed solution; and adding the first mixed solution into the second mixed solution, and reacting under a heating condition to obtain the zirconium metal-organic framework loaded nano platinum catalyst. According to the invention, a zirconium metal-organic framework Zr-BBI is used as a carrier, and platinum nanoparticles are encapsulated in pore channels of the framework. In the Zr-BBI linker, the uncoordinated nitrogen atom of the bis-imidazole group can better anchor and stabilize the object platinum, and enhance the interaction with the subject. The strong interaction between the platinum and the Zr-BBI promotes the high dispersion of the platinum nanoparticles, and the Zr-BBI loaded platinum nanoparticles have uniform and small particle sizes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for preparing furfuryl alcohol by selective hydrogenation of furfural, and in particular to a zirconium metal-organic framework-supported nano-platinum catalyst and a preparation method and application thereof. Background Art

[0002] Lignocellulose-derived furfural is an important biomass platform molecule that is widely used as an intermediate product to provide a variety of products to the energy sector as well as the chemical and pharmaceutical industries. Furfural, as an α,β-unsaturated aldehyde, contains two unsaturated groups, C=O of the aldehyde group and C=C of the furan ring. Selective hydrogenation is the main route to efficiently convert furfural into high-value-added chemicals such as furfuryl alcohol, tetrahydrofurfuryl alcohol, furan, 2-methylfuran and cyclopentanone. Among them, furfuryl alcohol is considered to be a renewable key chemical intermediate and is widely used in the manufacture of crown ethers, adhesives, furan-based resins, synthetic fibers, fuels and additives. Due to the diversity of unsaturated groups, the selective hydrogenation of biomass furfural to produce furfuryl alcohol is challenging.

[0003] Although noble metal catalysts such as Pt, Pd, and Ru exhibit excellent hydrogenation performance, they are also prone to deep hydrogenation of C=C in the furan ring, resulting in low selectivity for furfuryl alcohol. Metal-organic frameworks, as a heterogeneous catalyst, have attracted increasing attention due to their clear active sites, high porosity, adjustable pore size, and rich pore structure. The encapsulation of platinum nanoparticles by metal-organic frameworks can effectively adjust the hydrogenation selectivity of platinum nanoparticle catalysts, inhibit the flat adsorption and activation of furan rings to a certain extent, and thus increase the selectivity of aldehyde hydrogenation. Although existing supported catalytic functional materials have achieved high furfuryl alcohol yields, most catalytic systems usually require relatively harsh reaction conditions, such as high reaction temperatures (180 ~ 210 ℃) and high hydrogen pressures (4 ~ 8 MPa), which will lead to high energy consumption, high costs, and strict operating conditions, limiting their practical applications. Therefore, it is still of great significance to develop new supported catalytic materials to achieve simple and efficient synthesis of furfuryl alcohol through furfural hydrogenation under mild conditions.

[0004] At present, the preparation of supported catalysts by encapsulating platinum nanoparticles in metal-organic frameworks has made significant progress and has shown excellent catalytic performance in many biomass conversion studies. However, these platinum atoms are usually located on the outer surface of the metal-organic framework and have a certain tendency to aggregate. In addition, although some platinum nanoparticles are encapsulated in the pores of the metal-organic framework, these metal atoms may leach out of the skeleton of the metal-organic framework due to the lack of interaction with the metal-organic framework. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a zirconium metal-organic framework-supported nano-platinum catalyst and a preparation method and application thereof, aiming to solve the technical problems of harsh conditions and unstable catalyst in the selective hydrogenation of furfural to furfural.

[0006] In a first aspect, the present invention provides a method for preparing a zirconium metal-organic framework-supported nano-platinum catalyst, comprising the following steps: dispersing platinum nanoparticles in a first solvent to obtain a first mixed solution; Mixing bisimidazolytetracarboxylic acid and zirconium salt, adding a second solvent and an acidity regulator and mixing them evenly to obtain a second mixed solution; The first mixed liquid is added into the second mixed liquid, and reacted under heating conditions to obtain a zirconium metal-organic framework-supported nano-platinum catalyst.

[0007] Preferably, the heating temperature is 115-130° C. and the heating time is 48-72 h.

[0008] Preferably, the preparation method of platinum nanoparticles comprises the following steps: dispersing PVP in ethylene glycol, adding H2PtCl6, ultrasonically dispersing and then heating to obtain a third mixed solution, adding acetone to the third mixed solution for precipitation, collecting solids by centrifugation, vacuum drying the solids, and washing with acetone to obtain platinum nanoparticles.

[0009] Preferably, the concentration of platinum nanoparticles in the first mixed solution is 1-2 mg / mL.

[0010] Preferably, the first solvent is DMF (anhydrous N,N-dimethylformamide).

[0011] Preferably, the bisimidazole tetracarboxylic acid is H4BBI (1,4-phenylbis(1H-imidazole-2,4,5-triyl)tetrabenzoic acid), the zirconium salt is ZrCl4, and the H4BBI and Zr in the second mixed solution are 4+ The molar ratio is 1:(1~2).

[0012] Preferably, the volume ratio of the second solvent to the acidic regulator is 5:(1-3); the second solvent is DMF, and the acidic regulator is formic acid.

[0013] In a second aspect, an embodiment of the present application provides a zirconium metal-organic framework-supported nano-platinum catalyst, which is prepared by the above-mentioned method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst.

[0014] In a third aspect, the present application provides an application of a zirconium metal-organic framework-supported nano-platinum catalyst in the preparation of furfuryl alcohol, comprising the following steps: S1, heating and reducing the zirconium metal-organic framework-supported nano-platinum catalyst in a reducing gas atmosphere, and cooling to obtain the reduced zirconium metal-organic framework-supported nano-platinum catalyst; S2. Mix furfural and the third solvent, add reduced zirconium metal-organic framework-loaded nano-platinum catalyst, add 20-40 mg reduced zirconium metal-organic framework-loaded nano-platinum catalyst per millimole of furfural, react under hydrogen atmosphere, reaction conditions: pressure 1-2 MPa, temperature 80-120°C, reaction time 6-24 h, cool after the reaction is completed, centrifuge and separate the reduced zirconium metal-organic framework-loaded nano-platinum catalyst to obtain furfuryl alcohol.

[0015] Preferably, the reducing gas in step S1 includes nitrogen and hydrogen, and the volume ratio of nitrogen to hydrogen is 1:(1-20).

[0016] Different from the existing technical solutions, the beneficial effects of this application include: 1. This application uses H4BBI and ZrCl4 as raw materials to prepare the zirconium metal-organic framework Zr-BBI, and uses Zr-BBI as a carrier to encapsulate platinum nanoparticles in the pores of the framework. In the Zr-BBI linker, the uncoordinated nitrogen atoms of the biimidazole group can better anchor and stabilize the guest platinum and enhance the interaction with the host. The strong interaction between platinum and Zr-BBI promotes the high dispersion of platinum nanoparticles, and the platinum nanoparticles loaded by Zr-BBI have a uniform and smaller particle size.

[0017] 2. The zirconium metal-organic framework-supported nano-platinum catalyst (Pt@Zr-BBI) prepared in this application has high catalytic activity and selectivity, and can realize the selective hydrogenation of furfural to prepare furfuryl alcohol under mild conditions. With isopropanol as solvent, the conversion rate of furfural can reach 100% after reacting at 120°C for 12 hours, and the selectivity of furfuryl alcohol can reach 94.5%.

[0018] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1XRD patterns of the zirconium metal-organic framework and the zirconium metal-organic framework supported platinum nanoparticle catalysts prepared in Example 1; Figure 2 is a SEM image of the zirconium metal-organic framework supported platinum nanoparticle catalyst prepared in Example 1; Figure 3 TEM image of the zirconium metal-organic framework supported platinum nanoparticle catalyst prepared in Example 1. DETAILED DESCRIPTION

[0021] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0023] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0024] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0025] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0026] Although existing supported catalytic functional materials have achieved high yields of furfuryl alcohol, most catalytic systems usually require relatively harsh reaction conditions, such as high reaction temperature (180 ~ 210 ℃) and high hydrogen pressure (4 ~ 8 MPa), which will lead to high energy consumption, high cost and strict operating conditions, limiting their practical application. Therefore, it is still of great significance to develop new supported catalytic materials to achieve simple and efficient synthesis of furfuryl alcohol through furfural hydrogenation under mild conditions.

[0027] At present, the preparation of supported catalysts by encapsulating platinum nanoparticles in metal-organic frameworks has made significant progress and has shown excellent catalytic performance in many biomass conversion studies. However, these platinum atoms are usually located on the outer surface of the metal-organic framework and have a certain tendency to aggregate. In addition, although some platinum nanoparticles are encapsulated in the pores of the metal-organic framework, these metal atoms may leach out of the skeleton of the metal-organic framework due to the lack of interaction with the metal-organic framework.

[0028] In order to solve the technical problems of harsh conditions and unstable catalysts in the selective hydrogenation of furfural to furfuryl alcohol, the present application provides a zirconium metal-organic framework-supported nano-platinum catalyst and its preparation method and application, wherein the present application uses H4BBI and ZrCl4 as raw materials to prepare a zirconium metal-organic framework Zr-BBI, uses Zr-BBI as a carrier, and encapsulates platinum nanoparticles in the pores of the framework. In the Zr-BBI linker, the uncoordinated nitrogen atoms of the biimidazole group can better anchor and stabilize the guest platinum and enhance the interaction with the host. The strong interaction between platinum and Zr-BBI promotes the high dispersion of platinum nanoparticles, and the platinum nanoparticles supported by Zr-BBI have a uniform and smaller particle size.

[0029] In a first aspect, the present invention provides a method for preparing a zirconium metal-organic framework-supported nano-platinum catalyst, comprising the following steps: dispersing platinum nanoparticles in a first solvent to obtain a first mixed solution; Mixing bisimidazolytetracarboxylic acid and zirconium salt, adding a second solvent and an acidity regulator and mixing them evenly to obtain a second mixed solution; The first mixed liquid is added into the second mixed liquid, and reacted under heating conditions to obtain a zirconium metal-organic framework-supported nano-platinum catalyst.

[0030] Preferably, the heating temperature is 115-130° C. and the heating time is 48-72 h.

[0031] Preferably, the preparation method of platinum nanoparticles comprises the following steps: dispersing PVP in ethylene glycol, adding H2PtCl6, ultrasonically dispersing and then heating to obtain a third mixed solution, adding acetone to the third mixed solution for precipitation, collecting solids by centrifugation, vacuum drying the solids, and washing with acetone to obtain platinum nanoparticles.

[0032] Preferably, the concentration of platinum nanoparticles in the first mixed solution is 1-2 mg / mL.

[0033] Preferably, the first solvent is DMF.

[0034] Preferably, the bisimidazolyl tetracarboxylic acid is H4BBI, the zirconium salt is ZrCl4, and the H4BBI and Zr in the second mixed solution are 4+ The molar ratio is 1:(1~2).

[0035] Preferably, the volume ratio of the second solvent to the acidic regulator is 5:(1-3); the second solvent is DMF, and the acidic regulator is formic acid.

[0036] In the technical solution of the embodiment of the present application, H4BBI and ZrCl4 are used as raw materials, DMF is used as solvent, and formic acid is used as acidic regulator to successfully synthesize the zirconium metal-organic framework Zr-BBI, and Zr-BBI is used as a carrier to encapsulate platinum nanoparticles in the pores of the framework. In the Zr-BBI linker, the uncoordinated nitrogen atom of the biimidazole group can better anchor and stabilize the guest platinum and enhance the interaction with the host.

[0037] In a second aspect, an embodiment of the present application provides a zirconium metal-organic framework-supported nano-platinum catalyst, which is prepared by the above-mentioned method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst.

[0038] In a third aspect, the present application provides an application of a zirconium metal-organic framework-supported nano-platinum catalyst in the preparation of furfuryl alcohol, comprising the following steps: S1, heating and reducing the zirconium metal-organic framework-supported nano-platinum catalyst in a reducing gas atmosphere, and cooling to obtain the reduced zirconium metal-organic framework-supported nano-platinum catalyst; S2. Mix furfural and a third solvent, wherein the third solvent is isopropanol, and then add a reduced zirconium metal-organic framework-loaded nano-platinum catalyst, add 20-40 mg of the reduced zirconium metal-organic framework-loaded nano-platinum catalyst per millimole of furfural, and react in a hydrogen atmosphere under the following reaction conditions: pressure 1-2 MPa, temperature 80-120°C, reaction time 6-24 h, cool after the reaction is completed, and centrifuge to separate the reduced zirconium metal-organic framework-loaded nano-platinum catalyst to obtain furfuryl alcohol.

[0039] Preferably, the reducing gas in step S1 includes nitrogen and hydrogen, and the volume ratio of nitrogen to hydrogen is 1:(1-20).

[0040] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0041] 1. Preparation method Example 1 (1) Preparation of platinum nanoparticles: 444 mg of PVP was dissolved in 20 mL of ethylene glycol, and then 101.5 mg of H2PtCl6 was added and fully dissolved by ultrasonication. The mixed solution was heated at 180°C for 10 min, and then precipitated with acetone and collected by centrifugation at 8000 rpm for 5 minutes. The collected solid was dried in a vacuum oven at 60°C overnight. The dried solid was further washed with acetone three times to remove excess free PVP, and then the obtained platinum nanoparticles (Pt NPs) were dispersed in a certain volume of anhydrous N,N-dimethylformamide (DMF) solvent for storage (concentration 2 mg / mL).

[0042] (2) Preparation of zirconium metal-organic framework supported platinum nanoparticle catalyst (Pt@Zr-BBI): 14 mg of organic ligand 1,4-phenylbis(1H-imidazole-2,4,5-triyl)tetrabenzoic acid (H4BBI) and 24 mg of zirconium tetrachloride were mixed in a 20 mL glass bottle, and then 5 mL of anhydrous N,N-dimethylformamide (DMF) and 1.5 mL of formic acid were added. After thorough mixing, 0.5 mL of Pt NPs (concentration 2 mg / mL) in step (1) was added. The glass bottle was placed in an oven at 120°C and heated at a constant temperature for 72 h, then cooled to room temperature, the solid was collected and washed with DMF, and dried to obtain the zirconium metal-organic framework supported platinum nanoparticle catalyst (Pt@Zr-BBI).

[0043] (3) Catalyst pretreatment: The dried sample was placed in a tubular furnace and heated from room temperature to 120 °C at a rate of 10 °C / min under nitrogen protection. The sample was then reduced in a hydrogen / nitrogen (50% v:v) atmosphere for 1 h. The sample was then cooled to room temperature and placed in a vacuum drying oven to obtain the reduced zirconium metal-organic framework-loaded platinum nanoparticle catalyst (Pt@Zr-BBI).

[0044] (4) Reaction of furfural catalytic hydrogenation to prepare furfural alcohol: 1 mmol furfural, 1 mmol dodecane and 10 mL isopropanol were placed in an autoclave reactor with dodecane as an internal standard. Then 20 mg of reduced zirconium metal-organic framework-supported platinum nanoparticle catalyst (Pt@Zr-BBI) was added to the above liquid. After the autoclave reactor was closed, 1.5 MPa of hydrogen was introduced into it. The temperature was then heated at 600 rpm with stirring. The reaction started when the reaction temperature reached 80°C. After reacting for 24 h, the reaction was cooled to room temperature and the reduced zirconium metal-organic framework-supported nanoplatinum catalyst was separated by centrifugation to obtain furfural alcohol.

[0045] Example 2 The difference between Example 2 and Example 1 is that the reaction temperature used in the catalytic hydrogenation of furfural to prepare furfuryl alcohol is 100°C, and the other steps are the same as in Example 1.

[0046] Example 3 The difference between Example 3 and Example 1 is that the reaction temperature used in the reaction of catalytic hydrogenation of furfural to prepare furfuryl alcohol is 120°C, and the other steps are the same as in Example 1.

[0047] Example 4 The difference between Example 4 and Example 3 is that the reaction time used in the catalytic hydrogenation of furfural to prepare furfuryl alcohol is 6 hours, and the other steps are the same as those in Example 3.

[0048] Example 5 The difference between Example 5 and Example 3 is that the reaction time used in the catalytic hydrogenation of furfural to prepare furfuryl alcohol is 9 hours, and the other steps are the same as those in Example 3.

[0049] Example 6 The difference between Example 6 and Example 3 is that the reaction time used in the catalytic hydrogenation of furfural to prepare furfuryl alcohol is 12 hours, and the other steps are the same as in Example 3.

[0050] Example 7 The difference between Example 7 and Example 3 is that the reaction time used in the catalytic hydrogenation of furfural to prepare furfuryl alcohol is 15 hours, and the other steps are the same as in Example 3.

[0051] Example 8 The difference between Example 8 and Example 6 is that 30 mg of zirconium metal-organic framework-supported platinum nanoparticle catalyst (Pt@Zr-BBI) is added in the reaction of catalytic hydrogenation of furfural to prepare furfuryl alcohol, and the other steps are the same as those in Example 6.

[0052] Example 9 The difference between Example 9 and Example 6 is that 40 mg of zirconium metal-organic framework-supported platinum nanoparticle catalyst (Pt@Zr-BBI) is added to the reaction of catalytic hydrogenation of furfural to prepare furfuryl alcohol, and the other steps are the same as those in Example 6.

[0053] Comparative Example 1 In Comparative Example 1, furfural was catalytically hydrogenated using platinum nanoparticles alone, and the specific steps were as follows: (1) Preparation of platinum nanoparticles: 444 mg of PVP was dissolved in 20 mL of ethylene glycol, and then 101.5 mg of H2PtCl6 was added and fully dissolved by ultrasonication. The mixed solution was heated at 180°C for 10 min, and then precipitated with acetone and collected by centrifugation at 8000 rpm for 5 minutes. The collected solid was dried in a vacuum oven at 60°C overnight. The dried solid was further washed with acetone three times to remove excess free PVP, and then the obtained platinum nanoparticles (Pt NPs) were dispersed in a certain volume of anhydrous N,N-dimethylformamide (DMF) solvent for storage (concentration 2 mg / mL).

[0054] (2) Reaction of furfural catalytic hydrogenation to prepare furfural alcohol: 1 mmol furfural, 1 mmol dodecane and 10 mL isopropanol were placed in a tank reactor, and 1 mg platinum nanoparticles (Pt NPs) catalyst was added to the above liquid. After the tank reactor was closed, 1.5 MPa of hydrogen was introduced into it, and then heated to 120°C under stirring at 600 rpm for 12 hours. After the reaction was completed, the reaction was cooled to room temperature, and the reduced zirconium metal-organic framework-supported nanoplatinum catalyst was separated by centrifugation to obtain furfural alcohol.

[0055] Comparative Example 2 In Comparative Example 2, UiO-66-loaded platinum nanoparticles were used to catalyze the hydrogenation of furfural, and the specific steps were as follows: (1) Preparation of platinum nanoparticles: 444 mg of PVP was dissolved in 20 mL of ethylene glycol, and then 101.5 mg of H2PtCl6 was added and fully dissolved by ultrasonication. The mixed solution was heated at 180°C for 10 min, and then precipitated with acetone and collected by centrifugation at 8000 rpm for 5 minutes. The collected solid was dried in a vacuum oven at 60°C overnight. The dried solid was further washed with acetone three times to remove excess free PVP, and then the obtained platinum nanoparticles (Pt NPs) were dispersed in a certain volume of anhydrous N,N-dimethylformamide (DMF) solvent for storage (concentration 2 mg / mL).

[0056] (2) Preparation of UiO-66 supported platinum nanoparticle catalyst (Pt@UiO-66): 16.6 mg of organic ligand terephthalic acid (H2BDC) and 23.3 mg of zirconium tetrachloride were mixed in a 20 mL glass bottle, and then 10 mL of N,N-dimethylformamide (DMF) and 1.37 mL of acetic acid were added. After thorough mixing, 0.5 mL of Pt NPs (concentration 2 mg / mL) in step (1) was added. The glass bottle was placed in an oven at 120°C and heated at a constant temperature for 24 to 48 hours, then cooled to room temperature, the solid was collected and washed with DMF, and Pt@UiO-66 was obtained after drying.

[0057] (3) Catalyst pretreatment: The dried sample was placed in a tubular furnace and heated from room temperature to 120 °C at a rate of 10 °C / min under nitrogen protection. It was then reduced in a hydrogen / nitrogen (50% v:v) atmosphere for 1 h. The sample was then cooled to room temperature and placed in a vacuum drying oven to obtain the reduced Pt@UiO-66.

[0058] (4) Reaction of furfural catalytic hydrogenation to prepare furfural alcohol: 1 mmol furfural, 1 mmol dodecane and 10 mL isopropanol were placed in an autoclave reactor with dodecane as an internal standard. 30 mg Pt@UiO-66 after reduction was added to the above liquid. The autoclave reactor was closed and 1.5 MPa of hydrogen was introduced into it. The temperature was then heated at 600 rpm with stirring. The reaction started when the reaction temperature reached 120 °C. After reacting for 12 h, the reaction was cooled to room temperature and the reduced Pt@UiO-66 catalyst was separated by centrifugation to obtain furfural alcohol.

[0059] 2. Test Method 1. Detection methods of X-ray powder diffraction (XRD), SEM, TEM, and EDS The X-ray powder diffraction (XRD) applied for uses a Rigaku Ultimate IV diffractometer with a Cu-Kα target (40kV, 40mA) to analyze the structure and purity of the material. The test range is 3~50° and the scanning speed is 10° / min.

[0060] In this application, a TESCAN MIRA LMS cold field emission scanning electron microscope (SEM) was used to observe the microscopic morphology and size of the material.

[0061] Transmission electron microscopy images, high-resolution transmission electron microscopy images (TEM) and element distribution (EDS) were obtained by a multifunctional field emission scanning electron microscope (TEM) (model: Thermo Fisher Talos F200s).

[0062] 2. Furfural conversion rate, furfuryl alcohol selectivity and furfuryl alcohol yield detection method The catalytic hydrogenation liquid product obtained in the examples of the present application was analyzed for composition using a GC-9790II gas chromatograph with a FID detector to calculate the reaction results.

[0063] III. Analysis of test results of various embodiments and comparative examples (1) The structure of the zirconium metal-organic framework supported platinum nanoparticle catalyst (Pt@Zr-BBI) synthesized in Example 1 was characterized by X-ray powder diffraction (XRD). Figure 1 As shown. The XRD spectra of zirconium metal-organic framework (Zr-BBI) and Pt@Zr-BBI are consistent with the spectra simulated by single crystal X-ray diffraction data, and the framework of the original MOF is not destroyed, indicating that the structure of the material is not affected after the zirconium metal-organic framework is loaded with platinum nanoparticles. The diffraction characteristic peaks of platinum nanoparticles in the XRD of Pt@Zr-BBI are not obvious, which may be due to the low concentration of platinum nanoparticles encapsulated in Zr-BBI and the material. On the other hand, it may be due to the small size of platinum nanoparticles, resulting in their characteristic diffraction peaks that cannot be detected or identified.

[0064] The morphology of the zirconium metal-organic framework supported platinum nanoparticle catalyst (Pt@Zr-BBI) and the size of the platinum nanoparticles were characterized by SEM and TEM tests. Compared with Zr-BBI, the rod-like morphology of Pt@Zr-BBI after loading was well maintained ( Figure 2 ). TEM analysis showed that platinum nanoparticles were uniformly dispersed in Zr-BBI, with an average size of about 4.1 nm. EDS further confirmed the uniform distribution of platinum in the material ( Figure 3 ).

[0065] (2) In Examples 1 to 3, the reaction temperatures for preparing furfuryl alcohol by catalytic hydrogenation of furfural were 80°C, 100°C and 120°C, respectively. The furfural conversion and furfuryl alcohol selectivity in Examples 1 to 3 were tested, respectively. The test results are shown in Table 1 below.

[0066] Table 1 Effect of reaction temperature on furfural conversion and furfuryl alcohol selectivity

[0067] It can be seen from Table 1 that as the reaction temperature increases, the conversion rate of furfural increases and the reaction speed becomes faster. The reaction temperature of 120°C is the optimal temperature for preparing furfural alcohol from furfural.

[0068] (3) In Examples 3 to 7, the reaction times for preparing furfuryl alcohol by catalytic hydrogenation of furfural were 24 h, 6 h, 9 h, 12 h and 15 h, respectively. The furfural conversion and furfuryl alcohol selectivity in Examples 3 to 7 were tested, respectively. The test results are shown in Table 2 below.

[0069] Table 2 Effect of reaction time on furfural conversion and furfuryl alcohol selectivity

[0070] It can be seen from Table 2 that as the reaction time increases, the conversion rate of furfural increases, and when the reaction is carried out for 12 hours, the selectivity of furfural to furfuryl alcohol is the highest. However, when the reaction time continues to increase, the selectivity of furfuryl alcohol decreases, so the optimal reaction time is 12 hours.

[0071] (4) In Example 6 and Examples 8-9, the amount of zirconium metal-organic framework-supported platinum nanoparticle catalyst (Pt@Zr-BBI) added to the reaction of catalytic hydrogenation of furfural to prepare furfuryl alcohol was 20 mg, 30 mg and 40 mg, respectively. The furfural conversion and furfuryl alcohol selectivity in Example 6 and Examples 8-9 were tested, respectively. The test results are shown in Table 3 below.

[0072] Table 3 Effect of catalyst dosage on furfural conversion and furfuryl alcohol selectivity

[0073] It can be seen from Table 3 that when the catalyst dosage is 30 mg, the furfural conversion rate and furfuryl alcohol yield are the highest.

[0074] (5) In Comparative Example 1 and Comparative Example 2, platinum nanoparticles (Pt NPs) and UiO-66-loaded platinum nanoparticle catalysts (Pt@UiO-66) were used to catalyze the hydrogenation of furfural. The furfural conversion and furfuryl alcohol selectivity in Comparative Example 1, Comparative Example 2 and Example 8 were tested, and the test results are shown in Table 4 below.

[0075] Table 4 Effects of NPs and Pt@Zr-BBI on furfural conversion and furfuryl alcohol selectivity

[0076] It can be seen from Table 4 that compared with the single platinum nanoparticles (Pt NPs) and Pt@UiO-66 catalysts, the zirconium metal-organic framework supported platinum nanoparticle catalyst (Pt@Zr-BBI) can significantly improve its catalytic activity and selectivity. This shows that the strong interaction between platinum and Zr-BBI promotes the high dispersion of platinum nanoparticles, and the platinum nanoparticles supported by Zr-BBI have a uniform and small particle size. And through experiments, it was found that the use of other metals to replace zirconium cannot synthesize the same structure as H4BBI metal-organic framework.

[0077] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a zirconium metal-organic framework-supported nano-platinum catalyst, characterized in that: The steps include: dispersing platinum nanoparticles in a first solvent to obtain a first mixed solution; Mixing bisimidazolytetracarboxylic acid and zirconium salt, adding a second solvent and an acidity regulator and mixing them evenly to obtain a second mixed solution; The first mixed liquid is added into the second mixed liquid, and reacted under heating conditions to obtain a zirconium metal-organic framework-supported nano-platinum catalyst.

2. The method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst according to claim 1, characterized in that: The heating temperature is 115-130° C., and the heating time is 48-72 hours.

3. The method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst according to claim 1, characterized in that: The preparation method of the platinum nanoparticles comprises the following steps: dispersing PVP in ethylene glycol, adding H2PtCl6, ultrasonically dispersing and then heating to obtain a third mixed solution, adding acetone to the third mixed solution for precipitation, centrifuging and collecting solids, vacuum drying the solids, and washing with acetone to obtain platinum nanoparticles.

4. The method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst according to claim 1, characterized in that: The concentration of platinum nanoparticles in the first mixed solution is 1-2 mg / mL.

5. The method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst according to claim 1, characterized in that: The first solvent is DMF.

6. The method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst according to claim 1, characterized in that: The bisimidazolyl tetracarboxylic acid is H4BBI, the zirconium salt is ZrCl4, and the H4BBI and ZrCl4 in the second mixed solution are 4+ The molar ratio is 1:(1~2).

7. The method for preparing the zirconium metal-organic framework-supported nano-platinum catalyst according to claim 1, characterized in that: The volume ratio of the second solvent to the acidic regulator is 5:(1-3); the second solvent is DMF, and the acidic regulator is formic acid.

8. A zirconium metal-organic framework supported nano-platinum catalyst, characterized in that: The zirconium metal-organic framework-supported nano-platinum catalyst is prepared by the preparation method of the zirconium metal-organic framework-supported nano-platinum catalyst according to any one of claims 1 to 7.

9. Application of a zirconium metal-organic framework supported nano-platinum catalyst in the preparation of furfuryl alcohol, characterized in that: The steps include: S1. Heating and reducing the zirconium metal-organic framework-supported nano-platinum catalyst described in claim 8 in a reducing gas atmosphere, and cooling to obtain the reduced zirconium metal-organic framework-supported nano-platinum catalyst; S2. Mix furfural and the third solvent, add reduced zirconium metal-organic framework-loaded nano-platinum catalyst, add 20-40 mg reduced zirconium metal-organic framework-loaded nano-platinum catalyst per millimole of furfural, react under hydrogen atmosphere, reaction conditions: pressure 1-2 MPa, temperature 80-120°C, reaction time 6-24 h, cool after the reaction is completed, centrifuge and separate the reduced zirconium metal-organic framework-loaded nano-platinum catalyst to obtain furfuryl alcohol.

10. The use of the zirconium metal-organic framework-supported nano-platinum catalyst in the preparation of furfuryl alcohol according to claim 9, characterized in that: The reducing gas in step S1 includes nitrogen and hydrogen, and the volume ratio of nitrogen to hydrogen is 1:(1-20).

Citation Information

Patent Citations

  • Preparation method of catalyst containing imidazole and derivatives thereof

    CN103611575A

  • Preparation method of amino-functionalized UiO-66 loaded platinum-cobalt bimetallic nano-alloy catalyst

    CN116786169A

  • UiO-66-NH2 / Pt / UiO-66-NH2 catalyst as well as preparation and application thereof

    CN117504937A

  • Efficient carrier separation photocatalyst based on metal organic framework material and preparation method

    CN117861730A

  • Method of treating flammable catalyst

    CN1400056A